Determinación de la Viabilidad de Vibrio choleare O1 en los medios de transporte Amies y Stuar - Cevallos M., Ana (2002)
It was studied the time of permanence of Vibrio cholerae 01 in the transport media Amies, Amies with charcon and Stuart. Thus, the faecal samples of thirteen cholera patients were collected and transported in those media included Cary - Blair medium. Through the fortnight cultures of each sample, V. cholerae 01 was isolated as follow: during the firsts 30 days in Stuart medium (p=l.OO). During 45 days Cary-Blair medium (p=0.095) and during 60 days in Amies wilh charcoal medium (p=Ü.199). Results indicate that V. cholerae 01 could be transported in all the media evalualed, except in Amies medium. In those media V. chalerae 01 has recovered under its culturable and viable form during the study time.